Effects of industrial back-support exoskeletons on body loading and user experience: an updated systematic review. Issue 6 (3rd June 2021) - Kermavnar, Tjaša; de Vries, Aijse W.; de Looze, Michiel P.; O'Sullivan, Leonard W.
Abstract: This study is an updated systematic review of papers published in the last 5 years on industrial back-support exoskeletons. The research questions were aimed at addressing the recent findings regarding objective (e.g. body loading, user performance) and subjective evaluations (e.g. user satisfaction), potential side effects, and methodological aspects of usability testing. Thirteen studies of active and twenty of passive exoskeletons were identified. The exoskeletons were tested during lifting and bending tasks, predominantly in laboratory settings and among healthy young men. In general, decreases in participants' back-muscle activity, peak L5/S1 moments and spinal compression forces were reported. User endurance during lifting and static bending improved, but performance declined during tasks that required increased agility. The overall user satisfaction was moderate. Some side effects were observed, including increased abdominal/lower-limb muscle activity and changes in joint angles. A need was identified for further field studies, involving industrial workers, and reflecting actual work situations. Practitioner summary: Due to increased research activity in the field, a systematic review was performed of recent studies on industrial back-support exoskeletons, addressing objective and subjective evaluations, side effects, and methodological aspects of usability testing. The results indicate the efficiency of exoskeletons in back-load reduction and a need for further studies in real work situations. Abbrevaitions: BB: biceps brachii; BF: biceps femoris; CoM: centre of mass; DA: deltoideus anterior; EMG: electromyography; ES: erector spinae; ES-C: erector spinae-cervical; ESI: erector spinae iliocostalis; ESI-L: erector spinae iliocostalis-lumborum; ESL: erector spinae longissimus; ES-L: erector spinae-lumbar; ESL-L: erector spinae longissimus-lumborum; ESL-T: erector spinae longissimus-thoracis; ES-T: erector spinae-thoracic; GM: glutaeus maximus; LBP: low back pain; LD: latissimus dorsi; LPD: local perceived discomfort scale; LPP: local perceived pressure scale; MS: multifidus spinae; MSD: musculoskeletal disorder; M-SFS: modified spinal function sort; NMV: no mean value provided; OA: obliquus abdominis (internus and externus); OEA: obliquus externus abdominis; OIA : obliquus internus abdominis; RA: rectus abdominis; RF: rectus femoris; RoM: range of motion; SUS: system usability scale; T: trapezius (pars Ascendens and Descendens); TA: trapezius pars ascendens; TC: mid-cervical trapezius; TD: trapezius pars descendens; VAS: visual analog scale; VL: vastus lateralis; VM: vastus medialis